Panggilan Misi Melalui Pendidikan Agama Kristen Dalam Konteks Kehidupan Moderasi Beragama Di Bali - Ni Nyoman Fransiska (Predica Verbum: Jurnal Teologi dan Misi, 2024)
Diversity in Indonesia, apart from being unique for this country, can also give rise to conflicts that can end in war, one of the triggers is religious differences. In Bali, conflicts due to religious differences are not visible but can be felt through people's stereotyped attitudes and discrimination. Having a selective attitude towards friends since childhood is the beginning of bullying which not only hurts mental health, it can even lead to physical harm. This research aims to re-examine using qualitative research methods with library research techniques. The results of this research show that religious moderation in a pluralistic society in Bali can be implemented with the missiological role of Christian Religious Education to promote Christian values ​​as an opportunity. PAK missiology is realized by creating a harmonious and tolerant community environment with the local cultural wisdom that exists in Balinese society.